2008
DOI: 10.1242/jcs.030627
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of endothelial ephrin-B2 in adhesion and transmigration of EphB-receptor-expressing monocytes

Abstract: The vascular endothelium is a crucial interface that controls the recruitment of circulating leukocytes. Based on the luminal expression of the ephrin-B2 ligand by endothelial cells (ECs) and the expression of EphB receptors (EphBRs) by circulating monocytes, we hypothesized that EphBR-ephrinB interactions are involved in monocyte adhesion. Adhesion experiments with monocytic cells were performed on ECs that overexpressed either full-length ephrin-B2 or cytoplasmically truncated ephrin-B2 (ΔC-ephrin-B2). Atomi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
72
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 65 publications
(77 citation statements)
references
References 49 publications
5
72
0
Order By: Relevance
“…We have also shown that selected resting endothelial cell populations express ephrinB2 on their luminal surface and that circulating leukocytes express EphB receptors (28). These findings have shown that bidirectional signaling-dependent EphB4/ephrinB2 interactions control monocyte adhesion to and transmigration through endothelial cells (29). Correspondingly, EphB4 plays a pivotal role in the recruitment of monocytes to ephrinB2-positive endothelial cells to sites of ischemic arteriogenic vascular remodeling (30).…”
Section: Introductionmentioning
confidence: 83%
“…We have also shown that selected resting endothelial cell populations express ephrinB2 on their luminal surface and that circulating leukocytes express EphB receptors (28). These findings have shown that bidirectional signaling-dependent EphB4/ephrinB2 interactions control monocyte adhesion to and transmigration through endothelial cells (29). Correspondingly, EphB4 plays a pivotal role in the recruitment of monocytes to ephrinB2-positive endothelial cells to sites of ischemic arteriogenic vascular remodeling (30).…”
Section: Introductionmentioning
confidence: 83%
“…Two rare, events were observed where HUVEC cells formed a circular enclosure around a 22Rv1 EphB4 over-expressing cell, and a similar event was also found for 22 Rv1 (2013) shows is that knockdown of EphB4 inhibits the invasiveness and migratory capability of tumour cells, which has been shown in multiple studies to date [16][17][118][119]135]. However, we show that CIL is restored not because the invasiveness of EphB4 overexpressing tumour cells has been suppressed, but that the interaction of with EphB4-Fc [242]. They found that between 30 min and 2.5 h the ligand is internalised and accumulated in the perinuclear region, and 6.5 hours after treatment ephrin-B2 is almost entirely degraded [242].…”
Section: Discussionsupporting
confidence: 83%
“…[242]. This study also showed that EphB expressing monocytes preferentially adhered to and transmigrated through ephrin-B2 expressing endothelium [242]. These studies corroborate the pro-adhesive effect of forward EphB4 signalling through ephrin-B2 expressing and LNCaP display an adhesive attraction to an ephrin-B2 over-expressing HUVEC endothelium, through cell-cluster formation.…”
supporting
confidence: 74%
See 2 more Smart Citations